2020
DOI: 10.1039/d0ta01217c
|View full text |Cite
|
Sign up to set email alerts
|

Rational understanding of the catalytic mechanism of molybdenum carbide in polysulfide conversion in lithium–sulfur batteries

Abstract: The S-passivated Mo2C behaves like a transition metal sulfide with strong binding to LiPSs, a small LiPS conversion energy barrier, and a low Li2S decomposition barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Forinstance,first-principles calculations suggested the sulfurization of Mo 2 C( 101) precatalyst upon LiPS adsorption, where such sulfurized Mo 2 Ce xhibited advanced activity. [10] Exhaustive characterizations also confirmed the electrochemical phase evolution of Co 4 Np recatalyst toward CoS x in working Li-S batteries. [11] Our previous effort also revealed the sulfurized transformation of defective VSe 2 host upon cycling.…”
Section: Introductionmentioning
confidence: 67%
“…Forinstance,first-principles calculations suggested the sulfurization of Mo 2 C( 101) precatalyst upon LiPS adsorption, where such sulfurized Mo 2 Ce xhibited advanced activity. [10] Exhaustive characterizations also confirmed the electrochemical phase evolution of Co 4 Np recatalyst toward CoS x in working Li-S batteries. [11] Our previous effort also revealed the sulfurized transformation of defective VSe 2 host upon cycling.…”
Section: Introductionmentioning
confidence: 67%
“…Recent years have witnessed a growing interest in studying precatalysts for sulfur electrochemistry, as the phase reconstruction of electrocatalysts before and after cell cycling was disclosed from theoretical and experimental perspective. For instance, first‐principles calculations suggested the sulfurization of Mo 2 C (101) precatalyst upon LiPS adsorption, where such sulfurized Mo 2 C exhibited advanced activity [10] . Exhaustive characterizations also confirmed the electrochemical phase evolution of Co 4 N precatalyst toward CoS x in working Li–S batteries [11] .…”
Section: Introductionmentioning
confidence: 87%
“…The coordination state of Mo atoms on the surface of Mo-based materials has a significant impact on the adsorption and catalysis of LiPSs. For instance, Sun et al revealed that Mo 2 C (101) surfaces underwent a sulfurization process during the sulfur loading and the resultant sulfurized Mo 2 C showed a similar mechanism of adsorption and catalytic activity to that of TMDs [ 134 ] Material design is believed to be an effective strategy for promoting the performance of Mo-based materials in Li-S batteries ( Table 1 ). For example, the Mo-based materials are expected to have high electronic conductivity, strong affinity to LiPSs (or Li + ), excellent catalytic capability, large specific surface areas, and uniform loading (dispersion) to ensure full utilization of cathode sulfur, efficient capture of LiPSs and subsequent conversion, high energy density, and dendrite-free Li plating.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The coordination state of Mo atoms on the surface of Mo-based materials has a significant impact on the adsorption and catalysis of LiPSs. For instance, Sun et al revealed that Mo 2 C (101) surfaces underwent a sulfurization process during the sulfur loading and the resultant sulfurized Mo 2 C showed a similar mechanism of adsorption and catalytic activity to that of TMDs [ 134 ]…”
Section: Conclusion and Prospectsmentioning
confidence: 99%